THE USHNU OF HUÁNUCO PAMPA: INCA CEREMONIAL PLATFORM AS A PLACE OF LIBATION AND ADMINISTRATIVE-RELIGIOUS CENTER PLANNING IN CENTRAL ANDES - Pino Matos, José Luis (2013)
The proposal in this article is, that the architectural components of the ushnu platform of Huánuco Pampa are spatially associated with the surrounding landscape and that libation rituals were the most important public activity, of this mode, this platform, was built at the center of this settlement and served as planning principle of the Inca administrative-religious center of Huánuco Pampa.